Kebijakan Dividen terhadap Keputusan Investor dalam Membeli Saham Studi Kasus PT United Tractors Tbk (UNTR) - Sukmawan, Rendi; Dhamayanti, Damita (IPM2KPE, 2024)
This research aims to determine the influence of dividend distribution policies on investors' decisions in buying shares of PT United Tractors Tbk (UNTR). The research method used is a literature review by analyzing secondary data in the form of the Financial Report of PT United Tractors Tbk (UNTR) for the period 1992-2023 which was published on the Indonesia Stock Exchange website. The research results show that the dividend distribution policy has a significant influence on investors' decisions to buy company shares. The conclusion is that a stable and sustainable dividend distribution policy can increase the attractiveness of shares for investors and encourage their decision to buy shares. Keywords: Dividend Distribution Policy, Investor Decisions, Shares